Pengaruh Harga, Kualitas Pelayanan, Dan E-Promotion Terhadap Minat Beli Pengguna Aplikasi Shopee (Studi Kasus Pada Mahasiswa FEB Universitas Islam Malang) - Pramana, Adham Putra; Widarko, Agus; Rizal, Mohammad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study is aimed at FEB students, Islamic University of Malang. The type of research using a quantitative approach is the research used. The purpose of this study is to determine how much Price, Service Quality, e-Promotion on Consumer Purchase Interest. The independent variables used are Price, Service quality, e-Promotion, Consumer Purchase Interest is the dependent variable. The sample of this study consisted of 90 respondents who were consumers aged 19-24 years, FEB students, Islamic University of Malang who had or who often made purchases. Using a questionnaire as a data collection tool. Instrument test, Using the SPSS computer program, the data were analyzed using multiple linear regression analysis, traditional assumption test, determination test, f test, and t test. The findings of this study indicate that pricing has a major impact on consumer Purchase Interest, Service Quality, and e-promotion all have a significant impact on consumer purchase interest. price, service level, and Consumer Purchase Interest are influenced by e-Promotion simultaneously. Keywords: Workload, Work Environment and Employee Turnover Intention.